(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This study investigates the comparative effectiveness of interactive multi-resource teaching versus traditional textbook-based instruction for 10th grade English language learners in Uzbekistan. Using a mixed-methods approach with 30 participants across two classroom settings, the research reveals significantly improved learning outcomes in interactive environments, with 46,7% of students showing positive engagement compared to 30% in conventional classrooms. Quantitative and qualitative data demonstrates that supplementary materials, group activities, and real-world applications enhance both motivation and knowledge retention. The findings advocate for pedagogical reforms incorporating student-centered approaches in Uzbek secondary education. Future research directions should examine practical implementation challenges and the long-term effects of interactive methodologies across different regional contexts. This study contributes to the broader discourse on optimizing second language acquisition in developing countries’ educational system.